2016
DOI: 10.1155/2016/8734827
|View full text |Cite
|
Sign up to set email alerts
|

In Patients with Coronary Artery Disease and Type 2 Diabetes, SIRT1 Expression in Circulating Mononuclear Cells Is Associated with Levels of Inflammatory Cytokines but Not with Coronary Lesions

Abstract: While SIRT1 is significantly associated with atherosclerosis and diabetic complications, its relevance to coronary lesions in patients with coronary artery disease and type 2 diabetes has not been specifically investigated. Thus, we assessed SIRT1 expression in peripheral blood mononuclear cells in these patients. We found that SIRT1 expression did not significantly correlate with syntax scores from coronary angiography (p > 0.05). Notably, plasma levels of the inflammatory cytokines tumor necrosis factor-α, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
3
10
0
3
Order By: Relevance
“…The findings of Breitenstein et al () study showed that monocyte SIRT1 expression levels of CAD and acute coronary syndrome (ACS) patients are significantly lower in comparison with healthy subjects. In another study by Li, Ni, Guo, and Li (), the expression of SIRT1 in PBMCs of patients with CAD and Type 2 diabetes was significantly correlated with inflammatory cytokines (IL‐6, TNF‐α, MCP‐1, and high‐sensitive CRP) levels but not with the severity of coronary lesions.…”
Section: Discussionmentioning
confidence: 96%
“…The findings of Breitenstein et al () study showed that monocyte SIRT1 expression levels of CAD and acute coronary syndrome (ACS) patients are significantly lower in comparison with healthy subjects. In another study by Li, Ni, Guo, and Li (), the expression of SIRT1 in PBMCs of patients with CAD and Type 2 diabetes was significantly correlated with inflammatory cytokines (IL‐6, TNF‐α, MCP‐1, and high‐sensitive CRP) levels but not with the severity of coronary lesions.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Breitenstein et al demonstrated that Sirt1 mRNA expression is decreased in peripheral blood monocytes isolated from patients either with angiographically confirmed coronary artery disease and/or presenting with acute coronary syndrome compared with mono-cytes isolated from healthy subjects [68], and the expression of IL-6 was increased in patients with impaired Sirt1 expression. Furthermore, Li et al showed that Sirt1 expression in peripheral blood mononuclear cells was negatively correlated with the levels of plasma inflammatory cytokines and chemo-kines, including IL-6 and TNF-α, in patients with type 2 diabetes and coronary artery disease [69]. These data suggest that Sirt1 expression in monocytes or mononuclear cells negatively regulates inflammation and is involved in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Роботи, в яких когорту обстежуваних складали пацiєнти з поєднанням ЦД 2 типу та IХС [16,17], за бiльшiстю показникiв, зокрема рiвнем IЛ-6, ФНП-α та СРБ, вiдповiдають результатам нашого дослiдження i пiдтверджують їх ви-щу концентрацiю порiвняно з особами кон-трольної групи. Хоча мають мiсце i деякi розбiжностi.…”
Section: групи (табл 3)unclassified
“…Невизначени-ми є форми IХС у дослiджуваних, що могло вплинути на результати роботи. Вiдмiнно-стi з дослiдженням Y. Li [17] стосуються рiвня СРБ, який виявився вищим в групi хворих з iзольованим перебiгом IХС порiв-няно з IХС на фонi ЦД. В даному дослiдже-нi приймали участь госпiталiзованi до вiд-дiлення кардiоваскулярної хiрургiї хворi зi стенокардiєю та багатосудинним ураженням коронарних артерiй, третина з яких мали супутнiй рiзний за важкiстю i анамнестично нетривалий ЦД, що могло позначитись на отриманих даних.…”
Section: групи (табл 3)unclassified
See 1 more Smart Citation